Polylactic và blend của polylactci với polyetylen tỷ trọng thấp - Thủy, Nguyễn Thị; Tùng, Nguyễn Huy; Chương, Bùi (Vietnam Journal of Chemistry, 2014)
Blend of poly(l-lactide) (PLLA) and low density polyethylene (LDPE) were prepared by melt mixing in order to improve the brittleness and enhance the impact strength of PLLA. A reactive compatibilizer with glycidyl methacrylate or with maleic anhydride, PE-GMA or PE-MA, was required as a compatibilizer due to the immiscibility between PLLA and LDPE. They distribute to reduce the domain size of dispersed phase in blends. The presence of PE-GMA made increase considerably properties of blend:  the tensile and impact strength increased in turn 22% and 35%; especially, the elongation increased 60%. Contrary to PE-GMA, the properties of blend with PE-MA were almost unchanged. The effect of reactive compatibilizer on morphology of blends was also investigated by using SEM. Keywords: Poly(l-lactide), Low density polyethylene, Polymer blend, Compatibilization.